A SNP-based assay in a non model species: evolutionary lineage assignment of brown trout ancient DNA - Chat, Joëlle; Manicki, Aurélie (Conservation genetics resources, 2012)
A set of 12 single nucleotide polymorphisms selected for both confirming Salmo trutta identity and distinguishing the six European evolutionary lineages were included in a multiplex single-base primer extension assay to confidently assign brown trout ancient DNA to one of the six European haplogroups. The assignment rate reaches 75% for brown trout scales collected 40 years ago.